AN ANALYSIS OF STUDENTS' ABILITY IN WRITING USING NOUN PHRASE ON DESCRIPTIVE TEXT - Selli Wahyuni; Eliza; Merry Prima Dewi (ELLTER Journal, 2020)
This research is conducted because the researcher found some problems at the eleventh grade students at SMAN 1 Padang Gelugur in writing. The first problem was some of the students felt reluctant to write in English. The second problem was some of the students had limited vocabulary. And the last problem was some of the students still had difficulties to understand the correct form of using noun phrase. This study aimed to find out the level achivement of students’ ability in writing using noun phrase on descriptive text. The design of this research was descriptive quantitative. The population of this research were the eleventh grade students that consist of 111 students. The students were divided into four classes. The number of samples of this research were 27 students. The researcher used purposive sampling technique to determine the sample, because the researcher had some considerations, the reason were: it is because the students have already learned about noun phrase on descriptive text. Then some of the students did not have a good writing noun phrase on descriptive text. To collect the data, the researcher used writing test. There were 3 indicators of noun phrase. They were head, premodifier and postmodifier. Based on the result of the research, it was found that 54,5% of the students had written noun phrase in ‘head’ correctly. Then it was found that 53,6% of the students had written noun phrase in ‘premodifier’ correctly. And it was found 53,5% of the students had written noun phrase in ‘postmodifier’ correctly. In conclusion, the students ability in writing using noun phrase based on those three indicators above was 54% which mean the students ability was in fair level. Therefore, based on the result that has been obtained by the researcher, it is concluded that the students still have difficulties using correct form of noun phrase in writing.